mutations and aggressive histopathologic characteristics of radioiodine-refractory papillary thyroid cancer - Ju Yeon Pyo; Yoon Jin Cha; SoonWon Hong (Journal of Pathology and Translational Medicine)
Background Radioiodine (RI) ablation following thyroid-stimulating hormone suppression is an effective treatment for papillary thyroid cancer (PTC), typically leading to favorable outcomes. However, RI-refractory tumors exhibit aggressive behavior and poor prognoses. Recent studies highlight the role of genetic abnormalities in PTC signaling pathways, including the activation of telomerase reverse transcriptase (TERT), and the correlation of mutations with adverse outcomes. Methods This study analyzed mutations in BRAF V600E and the TERT-promoter genes, comparing clinicopathological features between RI-refractory and RI-responsive PTCs. Among 82 RI-refractory patients, formalin-fixed, paraffin-embedded tissues from initial surgeries were available for 26. Another 89 without distant metastasis over 5 years formed a matched RI-responsive control group. Results Histopathologically, RI-refractory PTCs showed increased frequencies of small tumor clusters without fibrovascular cores, hobnail features, and a high height-to-width ratio of tumor cells. These tumors were more likely to exhibit necrosis, mitosis, lymph node metastasis, extrathyroidal extension, and involvement of resection margins. TERT-promoter mutations were statistically significantly associated with these aggressive clinicopathologic features. Immunohistochemically, decreased expression of sodium iodide symporter and thyroglobulin stimulating hormone receptor proteins was common in RI-refractory PTCs, along with lower levels of oncogenic proteins such as vascular endothelial cell growth factor, vascular endothelial cell growth factor receptor 2, and nuclear factor kappa-light-chain-enhancer of activated B cells. Total loss of PTEN expression was occasionally observed. In contrast, all cases tested positive for cytoplasmic β-catenin. Conclusions RI-refractory PTCs are linked to TERT mutations and exhibit specific aggressive histopathologic features, particularly in tumor centers.